The institutional spheres of e-government usage - Kassim, Erne Suzila; Hussin, Husnayati (2009)
A large number ofstudies have been conducted in an attempt to investigate and understand the usage determinants ofe-government applications. However, there seems to be lack ofresearch that look into the factors of environment, termed as the institutional spheres, as most focus on technological, individual and organizational perspectives. Therefore, using institutional theory as a lens, a framework is proposed to consider the different institutional realms that will affect the decision to use the various types of e-governments applications. These aspects are drawn together into a model and its implications for future IS research are discussed.